Clinical and molecular analysis of smoothened inhibitors in Sonic Hedgehog medulloblastoma. Issue 1 (7th July 2021) - Pereira, Victor; Torrejon, Jacob; Kariyawasam, Dulanjalee; Berlanga, Pablo; Guerrini-Rousseau, Léa; Ayrault, Olivier; Varlet, Pascale; Tauziède-Espariat, Arnault; Puget, Stéphanie; Bolle, Stéphanie; Beccaria, Kevin; Blauwblomme, Thomas; et al.
Abstract: Background: Smoothened inhibitors (SMOi) have shown activity in Sonic Hedgehog (SHH) medulloblastoma, however this therapeutic class was not developed in children due to severe effects reported on growth. We hereby report long-term follow-up of young patients treated with SMOi for recurrent medulloblastoma. Methods: Clinical data on response and toxicity from patients treated with vismodegib or sonidegib from 2011 to 2019 for a SHH medulloblastoma were retrospectively reviewed. Methylation analysis and whole exome sequencing were performed whenever possible. Results: All patients with a somatic PTCH1 mutation responded to SMOi (6/8), including 2 prolonged complete responses. One patient was free of disease 8.2 years after treatment. SMOi was challenged again for 3 patients. Two of them had a response, one with SMOi alone, the other one in combination with temozolomide despite previous progression under monotherapy. SMO resistance mutations were found in patients from biopsy at relapse. Combination with temozolomide or surgery plus radiotherapy was associated with very long disease control in 2 patients. The most severe adverse events were myalgia and growth plate fusion with metaphyseal sclerosis. Normal growth velocity was recovered for 1 patient although her final height was below estimated target height. Conclusions: Targeting SMO in mutated PTCH1 is an interesting strategy for long-term responses. Combination of SMOi with chemotherapy or surgery and local radiotherapy is an appealing strategy to prevent early resistance and diminish SMOi exposure, especially in young patients. Inhibition of SHH pathway causes growth and development impairment but partial recovery of the growth velocity is possible.